THE INFLUENCE OF NUTRITION LABEL TOWARD CUSTOMER PURCHASE DECISIONS ON ANLENE LOW FAT HIGH CALCIUM MILK - B12111022, Ridiyat Fajar Noor Rifana (Jurnal Manajemen Update, 2015)
This study aim is to determine the influence of nutrition label towards customer purchase decision. The research methodology in this research is quantitative research methods, the research objects are Pontianak Anlene Customers with sample of 100 respondents. Data was collected through questionnaire. This research uses regression analysis to analyze the data.The study found that serving size has positive and significant influence on customer purchase decision both for under 50 years’ old respondents and more than 50 years old respondents. Number of servings per container has negative and not significant influence on customer purchase decision both for under 50 years old respondents and more than 50 years old respondents. And for nutrition content has positive and significant influence on customer purchase decision for under 50 years old respondents but for more than 50 years old respondents has positive and not significant result.Keywords: nutrition Label, serving size, number of servings per container, nutrition content, customer purchase decisions, milk product